Covid-19: Moving towards the new normal - David Briggs (ACHSM, 2020)
Since the last issue when we first spoke of the impact of Covid-19 we continue to be focused on addressing the challenges this virus has on health systems, nation states, communities, and people. The approach of countries and health systems has been variable as has the political interventions and interpretations of policy with some unfortunately placing parochial populism ahead of evidence and common sense......